The Constitutionality Of The Practice Of Euthanasia Against Parents In Maqashid Sharia And Human Rights - Candra, Anton Afrizal; Haji Abdullah, Raihanah Binti (Jurnal Hukum dan Peradilan, 2024)
Efforts to take a conscious action that can hasten the death of a person due to compassion and pity for the condition experienced by that person is called euthanasia or "qatlurrahmah" (killing out of compassion and sympathy). This study wanted to analyze whether or not a child should practice euthanasia against their parents who have been sick for a long time or suffer from chronic diseases that cannot be cured and even coma for a long time. The method used in this study is a normative legal method with a conceptual approach (conceptual approach) and legislation (statute approach). The results showed that the practice of euthanasia against parents was against maqashid sharia namely to realize the benefit of human life, especially the protection of the human body and soul (hifzhun Nafs), the right to live, and life as a form of protection of human rights as regulated in the Indonesian Constitution Article 28 A of the 1945 Constitution and reinforced by Article 28 I of the 1945 Constitution.